Draft Seventh Five Year Plan Andhra Pradesh 1985-90 Volume II Section IV Irrigation and Flood Control - Planning Commission (Planning Commission, 1985)
Till towards the close of the first half of the 19th Century, irrigation in the areas which now form Andhra Pradesh, was through large numbers of wells and tanks. The construction, by Sir Arthur Cotton, of the Godavari and Krishna anicuts in 1850's heralded a new era of large scale irrigation development. The anicuts and canals built during this period was all run of the river schemes and did not involve any large scale impounding of river waters behind storage dams. According to the irrigation Commission Report (1972), the net area irrigation in Andhra Pradesh was 23.18 lakhs hectares at the beginning of the First Five Year plan.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh